Penerapan Metode Eklektik untuk Memperoleh Kosakata Bahasa Arab pada Siswa Kelas 8 MTs Hidayatul Ummah Gresik - Qomaruddin, Farid (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2024)
This research is under the topic “Application of the Selective Methods to Acquire Arabic Vocabulary among Eighth Grade Students in Middle School at Hidayatul Umma Gresik. The focus of this research is on how to acquire Arabic vocabulary through a selective method. Hence, the researcher suggested that acquiring Arabic vocabulary by applying the selective method is an important matter to encourage the professor and students to pay more attention to applying the Arabic language with their vocabulary. The approach used in this research is the qualitative approach with the type of case study research. The aim of this research is to obtain descriptive data through interviews, observation, and documents on the application of the selective method to acquire Arabic vocabulary among eighth-grade students in Hidayatul Ummah Gresik. Among the most important results obtained by the researcher are: The researcher found shapes in vocabulary acquisition. There are different types of students’ ability to acquire their vocabulary during the process of teaching and learning the Arabic language, and for this reason the school encourages strong enthusiasm to make the students love Arabic.